PROGRAM PEMBERDAYAAN EKONOMI MANDIRI MELALUI BUDIDAYA PERIKANAN DAN PERKEBUNAN DALAM EMBER DI PANTI ASUHAN BUDI MULYA 2 - Rahmalia Syahputri; Nurfiana Nurfiana; Jaka Darmawan; Ari Widiantoko (Institute of Research and Community Outreach - Petra Christian University, 2021)
Budi Mulya 2 (BM2) orphanage is a social institution located in Bandar Lampung. To meet the operational needs of development, the day-to-day operations of the orphanage, as well as their development, BM 2 rely on donations provided by permanent and non-permanent donors, thus the cost of developing the homes and foster children is unpredictable, very small, and insufficient. For an institution to have sufficient funds for both physical and non-physical development to allow foster children can be maximized for their guidance process, it is necessary to plan and develop a focused and sustainable business. As one of the efforts is conducting a long-term three-year program to empower the economy independently through aquaculture and plantations in buckets. By doing this action, it is hoped we can build a community service and education institution that is dynamic and capable of accommodating and fostering many neglected children through an independent economic enterprise improvement program. This paper describes the results of the service during the first year of service activities; which are the construction and cultivation training, the first harvest, and several activities during the COVID-19 pandemic had been held. In addition, the skills of the caregiver and foster children improve in cultivating fish and plants in buckets. Abstrak: Panti asuhan Budi Mulya 2 (BM 2) adalah satu satu lembaga sosial yang berlokasi di Bandar Lampung. Dalam memenuhi kebutuhan operasional pembangunan, operasional sehari-hari panti dan anak asuh, serta pengembangannya, BM 2 mengandalkan donasi yang diberikan oleh Donatur tetap dan tidak tetap, sehingga biaya pengembangan panti dan anak asuh tidak stabil, sangat kecil, dan tidak mencukupi. Agar lembaga dapat memiliki dana yang cukup untuk pengembangan baik fisik dan non fisik, sehingga anak asuh dapat termaksimalkan proses pembinaannya, maka Perlu direncanakan dan dikembangkannya usaha yang terarah dan berkesinambungan. Sebagai salah satu upaya, untuk itu, telah dicanangkan program jangka panjang tiga tahun pemberdayaan ekonomi mandiri melalui budidaya perikanan dan perkebunan dalam ember. Melalui kegiatan ini diharapkan terbentuknya sebuah lembaga pengabdian dan pendidikan masyarakat yang dinamis dan mampu menampung dan membina banyak anak-anak terlantar melalui program peningkatan usaha ekonomi mandiri. Tulisan ini memaparkan hasil pengabdian selama tahun pertama kegiatan pengabdian; antara lain telah diselenggarakannya pembangunan dan pelatihan budidaya, panen pertama, dan beberapa kegiatan pada masa pandemic COVID-19. Selain itu, bertambahnya keterampilan Pengasuh dan Anak asuh dalam membudidayakan ikan dan tanaman dalam ember.